PENGARUH KEPEMIMPINAN DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PT KERETA API INDONESIA (Persero) DI KANTOR DAOP IV SEMARANG - Sami'an Sami'an; Estu Aprilian NW (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2013)
The aims of the research are to know: 1) The significant influence between leadership andworkers’ job of PT Kereta Api Indonesia (Persero) at office DAOP IV Semarang. 2) Thesignificant influence between leadership and supervision of workers’ job of PT Kereta ApiIndonesia (Persero) at office DAOP IV Semarang. 3) Which variables between leadership andsupervision at once that giving dominant influence towards workers’ job at PT Kereta ApiIndonesia (Persero) at office DAOP IV Semarang. The population of this Descriptive researchis all of workers at PT Kereta Api Indonesia (Persero) at office DAOP IV Semarang. It took114 workers as a samples by using random sampling technique. Data collection used questionaereand will analyzed by using doubled regresi linie ,test F, test t, test R2, and relative and efektivecontribution. Research conclusion, those are; 1)” There is significant leadership’ influencetowards workers’ job can be received. It is based on doubled regresi linier analysis (test/uji t) isknown that thitung ttabel, that is: 2,862 2,000 and significance value 0,05, that is:0,001 wth efective contribution 25,34%. 2) “ There is significant influence towards workers’job can be received. It is based on doubled regresi linier analysis (test/uji t) is known thatthitung ttabel, that is 3,653 2,000 and significance value 0,05, that is 0,000 withefective contribution 27,96%. 3) “ There is significant leadership’ influence and supervisionat once towards workers’ job can be received. It is based on variation doubled regresi linieranalysis (test/uji F) is known that Fhitung Ftabel,that is 11,914 3,150 and significance 0,05, that is 0,000. 4) Test result of determination coefisient (R2) is 0,533 showed that thesignificance of leadership influence and job supervision at once towards workers’ job is 53,3%,while 46,7% the rest is influenced by another variable that has not investigated.